(untitled) (Educational Knowledge, 2017)
This article is the product of a Graduation Seminar for the Bachelor’s Degree in Special Education with an emphasis on Multiple Disabilities at the University of Costa Rica. Its main objective was to analyze the teaching strategies used in literacy instruction for students with multiple disabilities. The research adopted a qualitative perspective with a phenomenological design. Eight teachers from the Carlos Luis Valle Masis Special Education Center in Costa Rica participated in the study. Throughout their professional careers, they had successfully taught reading and writing to students with this condition. Data analysis was conducted using triangulation, comparing information obtained from different sources (eight teachers) through two techniques (interviews and self-reports). This analysis was based on the sequence of actions to follow in the phenomenological analysis of data obtained in an interview, as proposed by Mari, Bo, and Climent (2010). The results show that for students with multiple disabilities to access literacy learning, three conditions are necessary: ​​the characteristics of the teaching staff, the specific needs of the students, and the support system. Regarding strategies—that is, the actions taken to achieve the objectives of the educational process—teachers highlight three basic aspects: a thorough diagnosis, the selection of the method based on the students’ characteristics, and the adaptation of the technique to their particular communication system.